2022
DOI: 10.1136/bmjmed-2022-000152
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial cancer: molecular classification and future treatments

Abstract: The treatment for endometrial cancer is rapidly evolving with the development of molecular analysis and novel strategies. Surgical resection, cytotoxic chemotherapy, endocrine or hormonal treatment, and radiation have been the staples of treatment for decades. However, precision based approaches for tumours are rapidly becoming a part of these strategies. Biomarker driven treatments are now a part of primary and recurrent treatment algorithms. This review aims to describe the current state of molecular analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 92 publications
0
43
0
Order By: Relevance
“…These findings guide stratification of patients as low, intermediate, or high-risk for extra-uterine disease or recurrence and in need of adjuvant therapies after surgery. Generally, low risk patients are recommended for observation alone while those with higher risk due to advanced FIGO stage, aggressive histology, high grade, or deep myometrial invasion are advised for more aggressive adjuvant therapies [ 22 ]. The importance of adjuvant therapy such as external beam pelvic radiotherapy, vaginal brachytherapy, chemotherapy, and combined chemotherapy and radiotherapy in higher risk patients have been evaluated in several studies such as GOG 258 and PORTEC-3 and have established current standards of care based on histopathology and stage [ 23 , 24 ].…”
Section: Current Histopathologic Classification Of Endometrial Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…These findings guide stratification of patients as low, intermediate, or high-risk for extra-uterine disease or recurrence and in need of adjuvant therapies after surgery. Generally, low risk patients are recommended for observation alone while those with higher risk due to advanced FIGO stage, aggressive histology, high grade, or deep myometrial invasion are advised for more aggressive adjuvant therapies [ 22 ]. The importance of adjuvant therapy such as external beam pelvic radiotherapy, vaginal brachytherapy, chemotherapy, and combined chemotherapy and radiotherapy in higher risk patients have been evaluated in several studies such as GOG 258 and PORTEC-3 and have established current standards of care based on histopathology and stage [ 23 , 24 ].…”
Section: Current Histopathologic Classification Of Endometrial Cancermentioning
confidence: 99%
“…However, over the past decade, several groups have demonstrated that certain molecular subtypes of endometrial cancer can have a substantial impact on prognosis, recurrence, and survival outcomes in various cohorts of patients [ 25 ]. Molecular analysis and molecular-driven treatments have become an important aspect of patient-directed care in endometrial cancer, offering the potential for more personalized therapeutic strategies [ 22 , 26 , 27 , 28 , 29 , 30 ]. In addition, clinical trials investigating more personalized therapeutic strategies or different systemic treatment options in patients with advanced/recurrent endometrial carcinoma based on molecular profiles are in progress.…”
Section: Current Histopathologic Classification Of Endometrial Cancermentioning
confidence: 99%
See 3 more Smart Citations